FUZZY DECISION MAKING FOR INPATIENT BOARDING: CASE OF A TUNISIAN HOSPITAL - Masmoudi, Malek; Chalgham, Marwa; Ben Houria, Zeineb (International Journal of Industrial Engineering: Theory, Applications and Practice, 2018)
Patients wait too much time in the emergency department to be redeployed to inpatient units, in departments related to their pathologies if available or other departments. This problem is called inpatient boarding and is one of major cause of overcrowding in hospitals. In this paper, we deal with the inpatient boarding problem and address the issue of decision-making problem while experts’ judgments are imprecise. We provide fuzzy multiple criteria decision making methodology-based heuristic that combines fuzzy sets with Analytical Hierarchy Approach and Technique for Order Performance by Similarity to Ideal Situation. The emergency department of Habib Bourguiba Hospital in Sfax in Tunisia is considered as a case study. Numerical examples are tested to show the advantages and efficiency of the proposed methodology.